If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y-8=143(y+5)
We move all terms to the left:
y-8-(143(y+5))=0
We calculate terms in parentheses: -(143(y+5)), so:We get rid of parentheses
143(y+5)
We multiply parentheses
143y+715
Back to the equation:
-(143y+715)
y-143y-715-8=0
We add all the numbers together, and all the variables
-142y-723=0
We move all terms containing y to the left, all other terms to the right
-142y=723
y=723/-142
y=-5+13/142
| 6+5b+3b=6-7b | | 92=9/5x | | 3.8+10m=6.54 | | 1-8x+x=5(7x-8)-5(5x+2) | | r-4/3=2 | | (x+1/2)=4x-3 | | (x)=-37 | | (k+7)^2=40 | | 8(-4+3x)=25+5x | | 38+2v=6(6v-5) | | z=-1.84z2= | | 9/v=3 | | n-20=8 | | -105=-5(1-4n) | | -6+7n=5n+2 | | 8x-(2x-4)=3(x-6) | | 95=5(3+8m) | | 15+x=20x | | 200m-125m+48000=50250-175m | | g+-9=-6.05 | | x+3/2x=5 | | 3(8x-1)=-99 | | -6(-2a+3)=-90 | | (7x-4)/(10x-6)=-7 | | −16−6v=−2(8v−7) | | 9-d=1 | | 2=u-6/2 | | 2/5y=-6 | | 4-6(n-5)=82 | | 22=-4x+8+6x | | 4(1+4r)+4=40+8r | | x+0.13x=11.23 |